2018
DOI: 10.29261/pakvetj/2018.034
|View full text |Cite
|
Sign up to set email alerts
|

Healing of Growth Plate Cartilage by Hypoxia Inducible Factor-1α Inhibitor Apigenin on Thiram Induced Tibial Dyschondroplasia

Abstract: Healing of growth plate cartilage by hypoxia Inducible Factor-1α inhibitor Apigenin on Thiram induced Tibial Dyschondroplasia. Pak Vet J, 38(2): 143-148. http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…There were significant variations in the ALP, AST, and ALT levels in TD-affected chickens revealing a possible liver injury. These findings are in accordance with previous studies where a decreased ALP and increased ALT and AST levels were reported in thiram-induced TD chickens [12,45]. After the osthole treatment, the levels of serum enzymes were significantly restored.…”
Section: Discussionsupporting
confidence: 93%
“…There were significant variations in the ALP, AST, and ALT levels in TD-affected chickens revealing a possible liver injury. These findings are in accordance with previous studies where a decreased ALP and increased ALT and AST levels were reported in thiram-induced TD chickens [12,45]. After the osthole treatment, the levels of serum enzymes were significantly restored.…”
Section: Discussionsupporting
confidence: 93%
“…Some reports showed that it interacts with GP and disturb the metabolism and the development of chondrocytes to cause TD [25,26,27]. On the other hand, it is reported that thiram has noxious effects on liver [4,28,29,30], which release MDA as an end product during lipid peroxidation and ultimately result in oxidative imbalance [31,32]. Li et al [33] reported that thiram destroyed the oxidative balance through decreasing SOD and GSH-Px and induced oxidative processes in chicken liver such as lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Three groups, the control, tibial dyschondroplasia (TD), and plastrum testudinis extract (PTE), were made containing an equal number of animals, i.e., (n = 100). The control group received a basal diet from day one until the end of the experiment whereas thiram was added in the basal diet of the TD and PTE groups at 50 mg/kg [41] during a 3-7 day interval, and, on the rest of the days, they received a normal diet. The PTE was supplied daily to the chickens orally from day 8-18 in the PTE group at 30mg/kg [38,42].…”
Section: Experimental Planmentioning
confidence: 99%